Whole-lung volume and density in spirometrically-gated inspiratory and expiratory CT in Systemic Sclerosis: correlation with static volumes at pulmonary function tests - Camiciottoli, G.; Diciotti, S.; Bartolucci, M.; Orlandi, I.; Bigazzi, F.; Mantucci-Cerinic, M.; Pistolesi, M.; Mascalchi, M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Spiral low-dose computed tomography (LDCT) permits to measure whole-lung volume and density in a single breath-hold. Objective: To evaluate the agreement between static lung volumes measured with LDCT and pulmonary function test (PFT) and the correlation between the LDCT volumes and lung density in restrictive lung disease. Design: Patients with Systemic Sclerosis(SSc) with(n=24) and without (n=16) pulmonary involvement on sequential thin-section CT and patients with chronic obstructive pulmonary disease(COPD)(n=29) underwent spirometrically-gated LDCT at 90% and 10% of vital capacity to measure inspiratory and expiratory lung volumes and mean lung attenuation(MLA). Total lung capacity and residual volume were measured the same day of CT. Results: Inspiratory [95% limits of agreement(95%LoA) - 43.8% and 39.2%] and expiratory(95%LoA -45.8% and 37.1%) lung volumes measured on LDCT and PFT showed poor agreement in SSc patients with pulmonary involvement, whereas they were in substantial agreement (inspiratory 95%LoA -14.1% and 16.1%; expiratory 95%LoA -13.5% and 23%) in SSc patients without pulmonary involvement and in inspiratory scans only (95%LoA -23.1% and 20.9%) of COPD patients. Inspiratory and expiratory LDCT volumes,MLA and their Δs differentiated both SSc patients with or without pulmonary involvement from COPD patients. LDCT lung volumes and density were not correlated in SSc patients with pulmonary involvement, whereas they did correlate in SSc without pulmonary involvement and in COPD patients. Conclusions: In restrictive lung disease due to SSc there is poor agreement between static lung volumes measured using LDCT and PFT and the relationship between volume and density values on CT is altered.